Analisis Kinerja Industri Perbankan Syariah - Idah Zuhroh (Universitas Muhammadiyah Malang, 2009)
This research aims to evaluate the performance of Sharia Banking industry from the aspects of : asset control, third party fund accumulation (DPK), and the ability of bank to distribute funds. Aside from that , the bank performance will be analyzed from financial ratio indicator referring to bank health assessement by Indonesian Central Bank using CAMEL. Sharia bank performance is emphasized more on it position in the National Banking Industry. Data gathered based on publication of Indonesion Central Bank statistics, while the sample is required only for examining the financial ratio based performance, comprising from the period of 2001-2005.The result of the research show that sharia banking has good performance indicating from the highest asset growth, third party fund accumulation (DPK), and also positively consistent funding and the increased tendency in market segment and position in the National Banking Industry, even if is relatively low (less than 2%). T test analysis with significant level of 5% show that sharia bank has leveled with National Banking Industry from the aspect of capital ratio, while asset quality perceived from non performing financing is higher than the National Banking Industry. From efficiency perspectives, Sharia Banking only has better performance than BUSN non Reserve, but is left behind compare to BPD.The ability in achieving profitability for Sharia Banking is leveled with Bank Persero, BUSN Reserve or even National Banking Industry. Compare to BUSN non Reserve, Sharia bank is significantly better in performance, however it is lagging compare to two other bank group , which are : Mixed Bank and Foreign Bank . The examination on liquidity reveals that banks in the industry are just over –liquid, while sharia bank reside under the minimum liquidity requirement, it is imposing that sharia bank has better FDR(Financing to Deposit compare to the other groups of bank in the National Banking Industry without having to sacrifice their asset quality. This is supported with low NPF bay Sharia Bank.Keywords : Sharia Bank, Performance, National Banking Industry.